2019
DOI: 10.7150/jca.35641
|View full text |Cite
|
Sign up to set email alerts
|

LAT, HOXD3 and NFE2L3 identified as novel DNA methylation-driven genes and prognostic markers in human clear cell renal cell carcinoma by integrative bioinformatics approaches

Abstract: Background: Abnormal DNA methylation of is one of the important mechanisms leading to tumor pathogenesis. The purpose of this study was to explore differentially methylated genes that may drive the development of renal clear cell carcinoma through a comprehensive analysis of the TCGA database. Materials and methods: Methylation data and RNA-seq data for clear cell renal cell carcinoma were downloaded from The Cancer Genome Atlas (TCGA). Differentially methylated genes and the differential genes associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…T cell is an important component of acquired immunity for hosts, which is able to be activated by phosphorylated LAT through TCR signaling pathway 38 . Wang et al elucidated prognostic risk models containing 3 genes by comprehensively analyzing methylation data and RNA-seq data for clear cell renal cell carcinoma (ccRCC) from TCGA database, and concluded that hypomethylation and over-expression of LAT resulted in poor OS of ccRCC 39 . Nevertheless, no studies so far have reported any correlation between LAT and HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…T cell is an important component of acquired immunity for hosts, which is able to be activated by phosphorylated LAT through TCR signaling pathway 38 . Wang et al elucidated prognostic risk models containing 3 genes by comprehensively analyzing methylation data and RNA-seq data for clear cell renal cell carcinoma (ccRCC) from TCGA database, and concluded that hypomethylation and over-expression of LAT resulted in poor OS of ccRCC 39 . Nevertheless, no studies so far have reported any correlation between LAT and HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Long et al used two DNA methylation-driven genes, SPP1 and LCAT, to construct two-gene signature which acted as an independent predictor for prognosis of liver cancer (Long et al, 2019). Methylated hub genes, including HOXD3, LAT, and NFE2L3, were proved to be a novel prognostic indicators in clear cell renal cell carcinoma (Wang et al, 2019). However, to our best knowledge, there is still a lack of research on screening DNA methylation-driven genes as prognostic biomarker in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Within each of the 6 categories of selected toxins, variation was observed in the extent of their potency against HK-2 cells, but overall, anticancer drugs and heavy metal-containing compounds were the most toxic. Within the anticancer drug category, in vivo animal and clinical studies have demonstrated potentially profound proximal tubular nephrotoxicity of idarubicin, 23,24 camptothecin, 25,26 vinblastine sulfate, 27 mitomycin C, 28,29 taxol, 30 doxorubicin-HCl, 24,31 sunitinib malate, 32,33 methotrexate hydrate, 28,34 and afatinib 35,36 These pharmaceutical drugs which possess vastly different mechanisms of action for their intended purposes of affecting the tubular and other parts of the kidney are not well studied. However, what they have in common is that these drugs and their metabolites are commonly eliminated through the renal system.…”
Section: Discussionmentioning
confidence: 99%